Ассоциация доменов хроматина с ядерным скелетом в клетках асцитной карциномы эрлиха. Анализ методом нуклеопротеид-целит-хроматографии - Сьяксте, Н.И.; Будылин, А.В. (Биополимеры и клетка, 1991)
Методом НПЦ-хроматографии исследовано распределение нуклеопротеидов различной прочности в изолированных ядрах и ядерном матриксе. В препаратах матрикса, полученных обработкой ядер ДНКазой I, обнаружены устойчивая к соли-мочевине (ДНК II) и неустойчивая (ДНК I) связи ДНК – матрикс. Все связи устойчивы к действию меркаптоэтанола, ЭДТА и низкой ионной силы. ДНК II чувствительна к действию нуклеазы S1. для ее разрушения необходимо плавление молекулы ДНК. Рестриктазы вызывают деградацию ДНК II с различной эффективностью: AluI, Sau3AI> >EcoRI, PstI, PvuII>HindIII, SalGI, BamHI. По совокупности свойств ДНК I и ДНК ІІ не соответствуют связям ДНК – матрикс, обнаруживаемым другими методами. Методом НПЦ-хроматографії досліджено розподіл нуклеопротеїдів різної міцності в ізольованих ядрах та ядерному матриксі. У препаратах матриксу, одержаних обробкою ядер ДНКзою І, виявлено стійкий до солі сечовини (ДНК II) та нестійкий (ДНК І) зв'язки ДНК – матрикс і фракція залишкового хроматину. Всі зв'язки стійкі до дії меркаптоетанолу, ЕДТА та низької іонної сили. ДНК II чутлива до дії нуклеази S1, для її зруйнування необхідне плавлення молекули ДНК. Рестриктази викликають деградацію ДНК II з різною ефективністю: ті, що пізнають тетрануклеотид, сильніше від атакуючих гексануклеотид, серед останніх EcoRI, PstI, PvuII більш ефективні, ніж HindIII, SalGI, ВатНІ. По сумі властивостей ДНК І та ДНК II не відповідають зв'язкам ДНК – матрикс, що виявлено другими методами. Distribution of the nucleoproteins, of different tightness has been studied in isolated nuclei and in the nuclear matrix by means of the NPC chromatography. A salt-urea resistant (DNAII) and sensitive (DNAI) DNA-matrix bonds and a fraction of residual chromatin have been detected in the matrix preparations obtained from DNAsel treated nuclei. All bonds are resistant to the action of mercaptoethanol, EDTA and low ionic strength. DNAII is sensitive to nuclease SI, the DNA melting is necessary for its destruction. Restrictases cause the DNAII degradation with unequal effectivity: the four base cutters are more effective as compared to the six base cutters. Among the latter EcoRl, PstI and PvuII degrade the bond to a greater degree than Hindlll, SalGl, BamHI. The totality of the DNAI and DNAII features indicate that these bonds do not correspond to differing types of the DNA-matrix boundings revealed by other methods.